2016
DOI: 10.1371/journal.pone.0149649
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Noninvasive Ventilation in Patients with “Do Not Intubate” Order in the Emergency Setting

Abstract: BackgroundNoninvasive ventilation (NIV) is being used increasingly in patients who have a “do not intubate” (DNI) order. However, the impact of NIV on the clinical and health-related quality of life (HRQOL) in the emergency setting is not known, nor is its effectiveness for relieving symptoms in end-of-life care.ObjectiveThe aim of this prospective study was to determine the outcome and HRQOL impact of regular use of NIV outcomes on patients with a DNI order who were admitted to the emergency room department (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 22 publications
0
21
0
1
Order By: Relevance
“…Vilaca et al [20] Portugal "Withholding therapy decision" group, comprised patients for whom a decision was made by the attending physician not to start or increase a life-sustaining intervention. "…”
Section: Country Description Of Dni Decision Making Processmentioning
confidence: 99%
“…Vilaca et al [20] Portugal "Withholding therapy decision" group, comprised patients for whom a decision was made by the attending physician not to start or increase a life-sustaining intervention. "…”
Section: Country Description Of Dni Decision Making Processmentioning
confidence: 99%
“… 35 Only one study has reported poor sleep during NIV in 76% of the studied patients. 36 In the OXYPAL study, particular attention will be paid to quality of sleep in all the included patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, invasive mechanical ventilation is considered a controversial intervention that deprives patients of their dignity and ability to recognise their family members 12. Indeed, advanced age or the presence of significant comorbidities are indications for DNI status, and in these cases, the use of NIV represents an alternative treatment.…”
Section: Discussionmentioning
confidence: 99%